Association of angiotensin ІІ type 1 receptor (A1166C) polymorphism with breast cancer risk: An update meta-analysis. (December 2015) - Chen, Fangguo; Chen, Guiling; Dou, Yan; Xu, Xinyun
Objective: Previous studies on the relationship between angiotensin ІІ type 1 receptor ( AT1R ) gene (A1166C) polymorphism and breast cancer did not reach the same conclusion. In the present study, we aimed to further evaluate the relationship between the AT1R gene A1166C polymorphism and breast cancer risk. Methods: We selected five case-control studies related to AT1R gene A1166C polymorphism and breast cancer by searching PubMed, EMBase, Chinese Biomedical Literature Database, Chinese CNKI, Web of Science, and the Wanfang database. We utilized Q-test and I 2 test to detect the heterogeneity between each study. A random-effects model (I 2 > 50%; p < 0.10) or a fixed-effects model (I 2 < 50%; p > 0.10) was utilized to merge the odds ratio (OR) and 95% confidence interval (CI) during the meta- analyses. Results: The present study included 972 patients with breast cancer and 1336 cancer-free control subjects. By meta-analysis, we found A1166C polymorphism was associated with decreased risk for breast cancer in Caucasian population in an additive model (C vs. T: OR = 0.77, 95% CI: 0.62–0.96, p = 0.02). However, we did not find associations in other genetic models (AC+CC vs. AA: OR = 0.78, 95% CI: 0.50–1.22, p = 0.28; CC vs. AA+AC: OR = 1.64, 95% CI: 0.94–2.85, p = 0.08). Conclusion: We concluded that AT1R gene A1166C polymorphism was associated with reduced risk for breast cancer.